How information processing and risk/benefit perception affect COVID-19 vaccination intention of users in online health communities - Liu, Hao; Gong, Liyue; Wang, Cao; Gao, Yunyun; Guo, Yi; Yi, Minhan; Jiang, Hao; Wu, Xusheng; Hu, Dehua (Frontiers in Public Health, 2023)
Background: During the COVID-19 pandemic, online health communities (OHCs) have become one of the most important platforms providing information sources for the public. Vaccines-related information on OHCs play a crucial role in users’ COVID-19 vaccine acceptance. Objective: To investigate the relationship between information processing, risk/benefit perception and the COVID-19 vaccination intention of OHCs users. Methods: The study conducted a cross-sectional questionnaire via an online survey among Chinese adults. A structural equation model (SEM) was used to examine the research hypothesis. Results: (1) Systematic information processing positively influences benefit perception, and heuristic information processing positively influences risk perception. (2) Risk perception is a negative determinant of vaccination intention, while benefit perception is a positive determinant of vaccination intention. Conclusion: Differences in information processing methods affect users’ perceptions of risk and benefit. Risk perception and benefit perception of the COVID-19 vaccine have opposite effects on users’ willingness to vaccinate. Benefit perception has more significant effects on willingness to vaccinate. Online health communities can provide more systematic cues and users should process information systematically to increase their perceived benefits, such increasing willingness to vaccinate against COVID-19.